Pelestarian Kesenian Randai di Sanggar Minang Saiyo Desa Sijantang Kota Sawahlunto - Megawati Marrita Putri; Desfiarni Desfiarni; Darmawati Darmawati (FBS Universitas Negeri Padang, 2015)
Abstract This study aimed to describe the preservation is done by Studio Minang Saiyo Village Sijantang Sawahlunto which is still used and exist in Sawahlunto. The research is a qualitative study using descriptive methods. Data collected through observation, interview, and literature study. The object of this study is Randai art studio located in the village of Minang Saiyo Sijantang Sawahlunto. These results indicate that the preservation of traditional arts in studio Minang Randai Saiyo has happened the development of the number of users, the expansion of the region and increase the number of actors performances. From 2001 until now the art Randai role in the wedding ceremony and reception guests who come to Sawahlunto. Users arts Randai Sijantang not only villagers but people outside the village Sijantang and Government Sawahlunto. Studio Minang Saiyo has expanded regions show, that as many as 8 regions consisting of Padang Gantiang border area Talawi Downstream with stone cage, Timpeh, Labuah Long, Kajai border area Lunto east to the village Sapan, Sindudua Village Guguak Sarai, Village Napar, Village Lumindai and the village of Tanah Datar Atar. Expansion of the area show performed by Studio Minang Saiyo began in 2014, the expansion pertujukan region can attract the connoisseurs of art and the growing number of actors in the arts Randai. Art displays Randai outside of Sijantang based on the desires of the Minang Studio Saiyo and demand from regions outside the village Sijantang to entertain the people and at the same time preserving Randai Arts in the village Sijantang. Keywords: Wildlife, art, randai, studio Minang Saiyo.